Study on the impact of renewable energy for rural development in Malaysia / Putri Nor Liyana Mohamad Radzi. - Putri Nor Liyana , Mohamad Radzi (2017)
Malaysia was blessed to fill with abundance of sustainable natural resources. Currently, Malaysia is highly dependence on conventional resources such as coal and natural gas in power generation. However, these resources emit high amount of Greenhouse Gases (GHG) into surrounding, affecting flora and fauna on Earth. These resources too experience depletion years by years and have to import by other country and the price to buy it is too expensive. To meet the energy demand of consumer within Malaysia without jeopardize mother nature, government had initiated a program by marking an aim to generate an energy based on eco-friendly and can be used for the long-term generation. Thus, introducing renewable energy is a best solution to overcome the crisis due to its potential as alternative sources to electrify urban and sub-urban areas. This research will study on estimating the effect that renewable energy could make to rural development, identify, quantify social and economic benefits from renewable energy by studying few case studies, and identify community awareness about implementation of renewable energy in Malaysia. The research was conducted by applying questioner survey to the people on the sites of the project. In addition, this research will analyze the perception and knowledge about these renewable energy resources and technology. To identify the social and economic opportunities in the community using renewable energy as alternative resources in Malaysia, the research will be focusing on both side of advantages and disadvantages on implementation renewable energy technology as an alternative resource other than conventional resources such as fossil fuels, oil, coal and natural gas and observing the outcome and contribution of renewable energy as new alternative energy towards the people in Malaysia. Keywords: Greenhouse gases, Renewable energy, rural development, Malaysia